BRIEF STUDY OF ANALYZING IDEOLOGICAL DIMENSION OF ISLAM RADICAL IN INDONESIA - Hergianasari, Putri (PEOPLE: International Journal of Social Sciences, 2019)
Terrorism is an ideology where the fulfillment of individual or group goals must be carried out even if it is carried out by acts of violence. One of fundamental aspect for human right clausal is the right of security. The act of terrorism, of course basically is violates basic human rights. As recently happened, a series of religious based of terrorism attacks has shaken Indonesia in May 13th–14th 2018. It was initially occurred in three churches in Surabaya. The bomb explodes took place at Immaculate Saint Marry Catholic Church, Indonesia Christian Church, and Surabaya Central Pentecost Church. To terrorist, as Abraham Lincoln said in term “indispensable necessity”. It is to describe about requirement of faith that cannot be negotiated because it involves their understanding on the basis of essential salvation. Many researcher, journalist and politician refuse to believe that this violence is happen because of the trigger of politic or religious ideology and prefer to explain it as a result of high economic disparity and social situation discrimination. However, terrorist feel that what they are doing is a truth. Thus, it is important to go beyond the concept that Jihadist is just a phenomenon because of insecurity based on internal disparity and discrimination problem, but it is a derivative of blind attraction of individual or group by big labels such as Daesh, ISIS or Al-Qaeda. Accordingly, this paper is written for explaining about the factors of violent extremism based Islamic religion, that flourishing recently by using three combination of theories as Primordialism, Constructivism, and Instrumentalism.